Microstructure and mechanical properties of WC-based cemented carbides with different binder phases - YANG Fang; GAO Yang; DU Peng; CHEN Leiming; CHENG Junwei (Fenmo yejin jishu)
The WC‒20Fe, WC‒20Ni, and WC‒20Co cemented carbides were prepared by gas pressure sintering at 1450 ℃ using the WC powders with the theoretical carbon content (mass fraction). The effects of metal binders on the microstructure and mechanical properties of the cemented carbides were investigated by X-ray diffractometer (XRD), scanning electron microscope (SEM), electron probe microanalysis (EPMA), and mechanical properties tester. The results show that, the brittle η-phase (Fe3W3C) appears in the WC‒20Fe alloys, and finer grains are observed due to the lower solubility of W (1.915% by mass) in Fe binder. However, the graphite phase (C) is detected in the WC‒20Co alloys, the solubility of W in Ni binder can reach to 10.753% by mass, resulting in the largest grain size and the lowest hardness. The WC‒20Co alloys show the two-phase region (WC+γ), which exhibit the highest bending strength and hardness of 2720 MPa and 934.41 kg∙mm‒2, respectively. The fracture mode of all the alloys can be described as the brittle fracture and intergranular fracture. Moreover, the fracture surface of the WC‒20Co alloys shows the obvious binder tearing character.